The distance to the Norma cluster and its relation to the great attractor region - Mutabazi, Tom (Department of Astronomy, 2015)
The Local Group's peculiar motion with respect to the cosmic microwave background has been measured with high precision and found to be ~627±22 km s-1, but the source of this motion is not clear. Studies to constrain the fractional contribution of the local mass overdensity, particularly in the Great Attractor region and the more distant Shapley Supercluster, remain contradictory. This work is an attempt to disentangle these contributions by measuring a redshift-independent distance to the Norma cluster, which lies at, or close to, the core of the Great Attractor, in order to determine its peculiar velocity. A reliable measurement of the distance and peculiar velocity of Norma will help clarify the velocity flows in the Great Attractor region. The challenge is with observing in the Zone of Avoidance since star crowding and Galactic extinction effects are severe at such low Galactic latitudes. High quality near-infrared images have been used in the photometric analysis for the Norma cluster sample so as to minimise the effect of Galactic extinction. In addition, the imaging cameras used have a small pixel scale resulting in well resolved images for reliable foreground star-subtraction hence accurate photometry. In order to determine the redshift-independent distance, I applied two independent, complemen- tary methods: the Fundamental Plane and the Tully-Fisher relations. The redshift-independent distance and the peculiar velocity of the Norma cluster were measured using 1) the Ks-band Fundamental Plane analysis for 31 galaxies using the 3.6m New Technology Telescope (NTT) at the European Southern Observatory (ESO) 2) the J- and Ks-band Fundamental Plane analysis for 31 galaxies using the Japanese 1.4 m InfraRed Survey Facility (IRSF) at the South African Astronomical Observatory (SAAO) 3) the combined NTT and IRSF Ks-band Fundamental Plane analysis for 41 galaxies 4) the Ks-band Tully-Fisher analysis for 12 galaxies using near-infrared images from the IRSF and HI profiles obtained from the 64-m Parkes radio telescope.